Ecoprint batik training to support ecotourism business in Sidoarjo - Nuril Lutvi Azizah; Uce Indahyanti; Vevy Liansari (Community Empowerment, 2022)
The Tanjung UMKM group in Sidokerto Village, Buduran District, Sidoarjo Regency, is a partner in the ecoprint training. In regard to the ecotourism industry that the Sidoarjo Regency Government is now developing, the concern raised is enhancing the abilities of the MSME group through ecoprints to boost product competitiveness. This program is carried out with ecoprints, which are inexpensive and environmentally friendly. This business will grow in natural tourism locations as souvenirs and regional features, in addition to being environmentally beneficial. The purpose of this service program is to train the local community how to make batik using natural dyes that are environmentally friendly. The MSME group was approached partially face to face throughout this activity. MSME partners were satisfied with this program, and there was a greater understanding of how to make batik from natural materials.